A cleaner process for valuable metals recovery from hydrometallurgical zinc residue. (10th November 2018) - Tang, Lei; Tang, Chaobo; Xiao, Jin; Zeng, Ping; Tang, Motang
Abstract: Most of hydrometallurgical zinc residues were stored in slag dump and unprocessed worldwide. Heavy metal and acid contained in these residues can be dissolved in rain water and then transfer to soil and groundwater system whereas threatening the health of aquatic systems and ecosystem. In this work, an innovative slag cleaning technique (reducing-matting smelting-thermal decomposition reduction) was proposed to harmlessly co-treat jarosite residue and lead silver residue, which can avoid environmental pollution and at the same time, effectively recover the valuable metal. Thermodynamic analysis and experimental results indicated that reducing atmosphere was a significant smelting parameter for recovery of valuable metal. Sulfur contained in various residues can be fixed in the form of solid sulfide (ferrous matte) without generation and emission of SO2 (g). Moreover, the matte product is a good collector for silver collection. In addition, various smelting parameters were investigated in detail to detect and obtain the smelting optimum condition: 12% coke addition, FeO/SiO2 = 1.6, CaO/SiO2 = 0.4, smelting temperature 1300 °C and smelting time 2.5 h. Under these smelting condition, the recovery of Cu, Zn, Pb and Ag can reach 98.82%, 98.84%, 90.35% and 97.17%. The feasibility and reliability of this innovative process were confirmed. The main phases in the slag are CaFe·2SiO2, NaCaAlSi2 O7 and silicate. It can be used in cement production so that the secondary pollution of slag can be avoided. Copper matte is comprised of FeS, Cu10 (Pb, Fe)S6, Cu5 FeS6 and Fe9 S11 . Ag is inlaid in copper mattes in the form of silver particles. Highlights: Innovative slag cleaning technique was presented to recover valuable metals. Thermodynamic analysis confirm feasibility and reliability of the experimental. Under optimum conditions, the recovery of valuable metals are more than 90%. Reduction-matting smelting avoids the harm of SO2 to the environment. Clean slag is very stable, avoiding secondary pollution.